Southern African liberation struggles contemporaneous documents, 1960-1994 - SADC Hashim Mbita Project (Dar es Salaam Mkuki na Nyota, 2014)
1. Introduction -- 2. Liberation war countries -- 3. Liberation war countries (continued) -- 4. Liberation war countries (continued) -- 5. Liberation war countries (continued) & frontline states -- 6. Frontline states (continued) -- 7. Frontline states (continued) & extension countries -- 8. Countries and regions outside SADC -- 9. Countries and regions outside SADC & international organisations.
Includes bibliographical references
Keywords: Democratization--Africa, Southern